‘We are in the process’: The exploitation of hope and the political economy of waiting among the aspiring irregular migrants in Nepal - Zharkevich, I (SAGE Publications, 2020)
‘We are in the process’ was the phrase used by my Nepali interlocutors, soon-to-be migrants, who were waiting for their departure abroad for months on end. Based on conversations with irregular migrants, this paper explores the relationship between time and power, focusing on the political economy of waiting. It suggests that making people wait has become a key technique of governmentality used by the migration industry actors to control aspiring migrants’ movement, exploit their desires and hopes, and extract surplus value, turning the migration industry in Nepal into a major system of profiteering. Forcing aspiring migrants to wait in a state of suspense (not boredom) for departures that are imminent but not certain, unscrupulous brokers create an affective state in suspended subjects, which allows those in power to prey on migrants’ vulnerability and their hope for a better life, pushing many of the aspiring migrants into grave debt.